Mapping optimal orthodontic implant sites in the palate using cone-beam computed tomography - Zhu, Zhengxian; Zhong, Lin; Zhao, Yicheng; Wang, Xiaoting; Qian, Wenhao; Ye, Niansong (Frontiers in Oral Health, 2024)
ObjectiveTo measure the palatal soft tissue thickness and cortical bone density to determine safe regions for the placement of orthodontic mini-implants and to examine the influence of sex and age on soft tissue thickness and cortical bone density.Materials and methodsCone-beam computed tomography images of 42 patients (22 males and 20 females), including 21 adults and 21 adolescents, were examined in this study. The palatal soft tissue thickness and cortical bone density were measured at the coronal planes between the premolars (P4–5), between the second premolars and first molars (P5–6), and between the first molars and second molars (P6–7).ResultsThe thickness of the soft tissue revealed similar coronal planes, but the bone density varied. The mean thickness was 3.8 mm at 0°–60° and 1.5 mm at 60°–90°. P4–5 had the highest bone density (>600 HU), decreasing toward P6–7 (<600 HU). Bone density decreased from 90° to 0° coronally, whereas the soft tissue thickness increased. Age, sex, and their interaction affected bone and soft tissues.ConclusionsIn general, areas with a high bone density tended to have thin soft tissue coronally, thus the preferred implant site tends to be more anterior to the P4–5 plane and closer to 60°–90°. Considering individual variances, mapping of the recommended regions for palatal mini-implants is suggested.